Peningkatan Motorik Halus Anak Melalui Kegiatan Bermain Papercraft (Penelitian Tindakan di TK Alam Rizkia, Depok) - Nurjannah, Dwi (PROGRAM STUDI PENDIDIKAN ISLAM ANAK USIA DINI (PIAUD), FAKULTAS ILMU TARBIYAH DAN KEGURUAN UIN SUNAN KALIJAGA YOGYAKARTA, 2018)
This paper presents the application of the intellectual conflict learning model in the context of the emotional development of children in the age of RA and their role in the interpersonal intelligence of students. This type of research is mixed methods. The topics of this study were 30 PIAUD students of the third semester. The instruments used in this study are questionnaire, observational sheet and document studies. Analysis of the data used in this study is qualitative data analysis by Miles and Huberman and analysis of quantitative data using simple regression tests. The results showed that: (1) the application of the intellectual conflict learning model had an impact on the cognitive aspects of the emotional development of children, affective and psychomotor in the emotional development of RA children; and (2) the intellectual conflict learning model provides a positive role for the interpersonal intelligence of the students.